2018
DOI: 10.1002/ijc.31614
|View full text |Cite
|
Sign up to set email alerts
|

Association between poor oral health and gastric cancer: A prospective cohort study

Abstract: Poor oral health may be involved in the pathogenesis of gastric cancer, however, some aspects have not been explored. Further, for previously studied aspects, for example, tooth-loss, the findings are inconsistent. We conducted a prospective cohort study of 19,831 participants from Uppsala, Sweden, cancer-free at baseline in 1973-1974 and followed until 2012 through linkage to national registers. We found that individuals with fewest teeth at baseline had an increased risk of gastric cancer relative to subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
27
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 30 publications
4
27
1
4
Order By: Relevance
“…Although it is difficult to provide clear evidence, furthermore, even though our result was statistically significant, the HR for frequent (≥3 times/day) toothbrushing was lower than those reported in previous studies (Ndegwa et al., 2018; Sato et al., 2011). We excluded a large number of subjects because of missing data for their oral health status (Table 1, Tables and ), which limits our assessment of the relationship between oral health behaviours and the risk for GI cancer.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Although it is difficult to provide clear evidence, furthermore, even though our result was statistically significant, the HR for frequent (≥3 times/day) toothbrushing was lower than those reported in previous studies (Ndegwa et al., 2018; Sato et al., 2011). We excluded a large number of subjects because of missing data for their oral health status (Table 1, Tables and ), which limits our assessment of the relationship between oral health behaviours and the risk for GI cancer.…”
Section: Discussioncontrasting
confidence: 98%
“…Moreover, in the Nurses’ Health Study, women with fewer teeth, which that study used as an identification of periodontal disease, had a higher risk than others of colorectal cancer (Momen‐Heravi et al., 2017). In a Swedish cohort study, poor oral hygiene indicators, such as tooth loss and denture‐associated lesions, were associated with an increased risk of gastric cancer (Ndegwa et al., 2018). A pooled analysis of data from the Atherosclerosis Risk in Communities study showed that periodontitis was associated with an elevated risk of lung cancer and colorectal cancer (Michaud et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Catherine and colleagues estimated 0.81 million cancers, mainly non-cardia GC, were caused by H. pylori in 2018 [ 54 ]. In addition, alcohol consumption, low intake of fruits and vegetables, obesity, poor oral health, low socioeconomic level, Epstein-Barr virus infection, radiation exposure, and family history of GC may increase the incidence of GC [ 2 , 53 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other confounders, such as oral hygiene habits [71], periodontal health status and severity of periodontitis, presence of other oral diseases, and dietary patterns [72], were disregarded. Tooth loss has been linked to an increased risk of GC development [73] and to an overall increased mortality rate [40]. Poor oral hygiene and tooth loss have also been linked to an increased risk of CRA occurrence [74,75].…”
Section: Discussionmentioning
confidence: 99%